Tinjauan Kaidah Fiqih Ju’alah dan Maisyir - Rahmah Kusuma, Nurul; Januri, Fauzan; Muharni, Yusraini (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2024)
Islamic teachings emphasize that all economic activities are based on sharia principles, which contain the muamalah principle that the substance of the meaning contained therein and the goals to be achieved end up in the goal of maqasid sharia and the benefit of the ummah. Fiqh rules are the basis related to legal issues, so they can detail fiqh problems in society, including ju'alah and maisyir which are often encountered due to technological developments and societal habits. The purpose of this research is to review the rules of ju'alah and maisyir fiqh. The research method used is to use a qualitative research method in the form of a literature study sourced from secondary data by reviewing various literature, such as books, articles and various kinds of relevant library materials. The results of this research are that the rules of fiqh, in the form of Qawa'id Al-Kulliyah, Qawa'id Al-Asasiyah, and Qawa'id furu' play a very important role in detailing problems related to ju'alah and maisy, so that people will be wiser in applying materials to provide solutions to various differences of opinion among ulama.